Research on the failure mechanism and control technology of surrounding rock in gob-side entry driving under unstable overlying strata. (August 2022) - Li, Guanjun; Wang, Xiangyu; Bai, Jianbiao; Wu, Bowen; Wu, Wenda
Highlights: The deformation of surrounding rock in gob-side entry driving under unstable overlying strata was observed. A UDEC Trigon model based on in-situ observation data and laboratory tests was constructed. The variation law of fracture development of surrounding rock, stress re-distribution in pillars during main roof movement was analyzed. A combined strata control method was proposed. Abstract: The main reason of gob-side entry deformation is surrounding rock movement near the goaf. During underground excavation, it is common that surrounding rock behavior and crack development under unstable overlying strata are substantially different from rock under strong and competent main roof. To study the failure mechanism due to main roof deformation near the edge of goaf, UDEC Trigon model was constructed with strong and thick hanging roof. Laboratory and Rock Quality Designation (RQD) results were used for model calibration. Results show that stress acting on the pillar increased dramatically due to roof subsidence prior to roof caving and breakdown. At the same time, considerable number of fracture developed in the roof and rib. After separation of failed roof, the influence on crack development decreased. Once the separated roof was stabilized, failure zone of surrounding rock stopped expanding. To manage the unsymmetrical deformation due to dynamic loading from hard main roof under gob-side entry driving, a combined strata control method was proposed, including roadway expansion, long cable bolt installation and roof cutting via blasting. Field trials prove that the optimized supporting plan can effectively control the large deformation of 9102 gateroad; and, the implementation of roof cutting can reduce gateroad failure from dynamic loading.